An Interdisciplinary Approach to Development of a New Combined Medicine for Musculoskeletal Disorders - Shapovalov, Valerii; Piontkovskyi, Valentyn; Huzovatyi, Oleksandr (SSP Modern Pharmacy and Medicine, 2023)
Musculoskeletal disorders represent a significant global health concern, affecting millions and straining healthcare systems. Addressing the complex nature of musculoskeletal disorders necessitates a multifaceted approach, one that integrates various scientific disciplines. This paper delves into the collaborative efforts employed in the development of a new combined medication tailored for musculoskeletal disorders. Bringing together expertise from pharmacology, biomedicine, physiotherapy, and bioinformatics, the research has forged a holistic pathway to medication synthesis. Key focus areas include the evaluation of molecular targets, ensuring optimal drug-drug interactions, and tailoring the therapeutic approach based on the individual patient's needs and the specific disorder's pathology. Furthermore, insights from physical therapy informed the drug development process, ensuring that the new medication aligns with rehabilitative approaches and promotes functional recovery. Advanced computational methods also played a pivotal role, enabling the prediction of drug efficacy, potential side effects, and patient response variability. Preliminary results suggest that this interdisciplinary strategy not only enhances the drug's therapeutic potential but also minimizes adverse reactions, paving the way for a more comprehensive and effective approach to managing musculoskeletal disorders. This research underscores the power of interdisciplinary collaboration on the relevance, necessity, and timeliness of the pharmaceutical development of a new combined medicine for musculoskeletal disorders based on known active pharmaceutical ingredients. The characteristics of active pharmaceutical ingredients (ketamine, analgin, diazepam) were studied in order to substantiate the composition based on a combination of evidence-selected active pharmaceutical ingredients. The composition, clinical and pharmacological properties, control regime, availability, areas of medical application, quality and safety profile were substantiated.